Characteristics of polarization of geomagnetic sudden commencements observed at Syowa Station - Nagano, Hiroshi; Araki, Tohru; Iyemori, Toshihiko; Fukunishi, Hiroshi; Sato, Natsuo; Ayukawa, Masaru (1986)
P(論文) In order to clarify local time dependence of polarization of geomagnetic sudden commencements (SC's) at Syowa Station, digital magnetic data obtained during the interval from April 1981 to January 1983 was statistically analyzed. The polarization in the horizontal plane is clockwise in the morning side and counterclockwise in the afternoon side from a view looking down onto the earth's surface. This is consistent with the statistical results from ground-based magnetic data (C. R. WILSON and M. SUGIURA : J. Geophys. Res., 66,4097,1961; T. NAGATA et al. : JARE. Sci. Rep., Ser. A, 3,64p., 1966) and from geostationary satellite magnetic data (H. NAGANO and T. ARAKI : J. Geophys. Res., 89,11018,1984). The relationship between the SC polarization sense in the horizontal plane and the pattern of SC wave form was examined. It is found that there is a fairly good correlation between them. departmental bulletin paper